The everyday political economy of private security - White, Adam (Policing and society, 2024)
In this article we map out a new research agenda for studying private security. We do so by bringing together a series of theoretical, methodological, and geographical ‘turns’ in this area of research that, in our view, signpost the way towards a deeper understanding of this market. The first turn is theoretical and concerns the shift from neoclassical economic interpretations of the market for security towards more political economic readings that excavate the various non-economic structures through which this market is constituted. The second turn is methodological and refers to the move from an (over)reliance on formal-legal, census-like data, towards the embrace of thicker qualitative (often ethnographic) data that gives voice to a range of ground-level perspectives in the market for security. The third turn is geographical and relates to how the long-standing focus on the Anglosphere is giving way to a more expansive map of the market for security that incorporates studies from across Africa, Asia, Continental Europe, and South America. We call this research agenda ‘the everyday political economy of private security’.